Preparation of nanostructured manganese-doped biphasic calcium phosphate powders via sol–gel method - Sopyan, Iis; Natasha, A. N. (Springer, 2009)
Biphasic calcium phosphate ceramics doped with manganese (Mn-doped BCP) were prepared by using chemical doping via sol–gel technique. Four different concentrations of manganese (2, 5, 10, and 15 mol%) have been successfully incorporated into biphasic calcium phosphate (BCP) phases. X-ray diffraction analysis revealed that the phases present in the Mn-doped BCP powders are hydroxyapatite and β-tricalcium phosphate. The Mn-doped powders are more crystalline than Mn-free BCP powder as its crystallinity increased with increasing Mn content. Fourier transform infrared spectrum corresponded to this result as the peak resolutions of PO4 bands are viewed with more intensity with the increased Mn. Particle size analysis resulted in nanoscale particles for the Mn-doped and Mn-free BCP powders. From field emission scanning electron microscope observation, Mn-doped BCP powders showed nanoscale individual particles but tightly agglomerated into microscale aggregates due to progressive fusion of particles. Hence, it can be concluded that Mn acts as calcination additives of the BCP powders.